Biomechanical factors influencing breaststroke turns by age-group-swimmers - Blanksby, B. A.; Simpson, J. R.; Elliott, B. C.; McElroy, K. (Journal of Applied Biomechanics, 1998)
Because turning can account for one-third of breaststroke race time in 25 m pools, it is possible that enhancing turning techniques can improve performance significantly. Underwater video cameras and a force platform were used to analyze turning techniques of 23 age-group breaststrokers during three 50 m push-start, maximum-effort swims. The criterion measure was the time elapsed between passing the 5 m mark on the approach and departure from the wall (5 m round-trip time [RTT]). Correlations revealed significant commonality of variance (p < .01) between the 5 m RTT and the 2.5 m RTT, 50 m time, average single-stroke velocity, peak reaction force, pivot time, impulse, peak horizontal velocity off the wall, arm and leg split-stroke resumption distances, surfacing distance, surfacing time, and horizontal velocity, height, and mass of the subjects. All swimmers achieved a net gain at the turn in that the mean 5 m RTT (20% of the distance) represented 18.26% of the total swimming time. Following stepwise regression, a successful turn was predicted by the equation 17.113 - 0.322 surfacing distance - 0.036 height - 0.723 surfacing horizontal velocity + 0.723 pivot time - 0.65 peak horizontal velocity.